Characterizing oogenesis and programmed cell death in the eastern tree hole mosquito Aedes (Protomacleaya) triseriatus - Airs, Paul M.; Nazarchyk, Michael J.; Tucker, Bradley J.; Bartholomay, Lyric C. (Frontiers in Insect Science, 2023)
Oogenesis in flies manifests as a carefully orchestrated cascade of developmental gates and growth events, punctuated by programmed cell death (PCD) and follicular resorption events. In anautogenous mosquitoes, a blood meal stimulates growth of primary follicles, but the timing of developmental stages is species-specific, and few species have been characterized. Here, we characterize the first gonotrophic cycle of oogenesis in Aedes triseriatus (Diptera: Culicidae), the principal vector of La Crosse Virus (LACV), a major cause of pediatric encephalitis in North America. We note significant differences in the timing and appearance of developmental stages from previous studies of other mosquito species, particularly Aedes aegypti. We also describe the appearance and timing of PCD events including atresia, nurse cell death, and follicular epithelium death and show that the majority of follicular epithelium cells do not undergo apoptosis during oogenesis but persist in the ovariole at least until the second gonotrophic cycle. This thorough characterization of oogenesis and PCD in Ae. triseriatus, through which LACV must persist in order to achieve filial infection, also serves as a baseline to study host-pathogen interactions during transovarial transmission.